2020
DOI: 10.32794/mr11250066
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pathophysiology: interactions of gut microbiome, melatonin, vitamin D, stress, kynurenine and the alpha 7 nicotinic receptor: Treatment implications

Abstract: As data emerges on the pathophysiological underpinnings of severe acute respiratory syndrome coronavirus (SARS-CoV)-2, it is clear that there are considerable variations in its susceptibility and severity/fatality, which give indications as to its pathophysiology and treatment. SARS-CoV-2 modulatory factors include age, vitamin D levels, cigarette smoking, gender and ethnicity as well as premorbid medical conditions, including diabetes, cancer, obesity, cardiovascular disease, and immune-compromised conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 82 publications
0
34
0
1
Order By: Relevance
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although positive biological effects have been reported for the administration of NO donors, further studies are required to better evaluate the levels of inflammatory mediators and the activity of important heme-containing enzymes, such as indoleamine 2,3–dioxygenase (IDO), directly involved in the inflammatory responses in respiratory viral infections ( Anderson and Reiter, 2020 ). During virus infection, a significant increase in the levels of inflammatory mediators can be observed, known as a “cytokine storm”, associated with endothelial and platelet activation; this can lead to vascular permeability, thrombocytopenia, shock (observed in severe cases), pulmonary hypertension and pneumonia ( Belladona and Orabona, 2020 ).…”
Section: No Potential Against Human Coronaviruses and Respiratory Virmentioning
confidence: 99%
“…Alterations in metabolism are crucial to immune cell function. All immune cells have to upregulate glycolytic metabolism in order to become activated whilst also maintaining their levels of OXPHOS [ 5 ]. As such, factors acting to regulate OXPHOS and glycolytic metabolism can dramatically influence immune cell function.…”
Section: Sars-cov-2 Entry and Pathophysiologymentioning
confidence: 99%
“…Although the importance of the initial rise in pro-inflammatory cytokines have been widely emphasized, there has been relatively little investigation of the common consequences arising, including (1) cytokine suppression of pineal gland melatonin and circadian dysregulation; (2) cytokine-induced gut permeability and dysbiosis with consequences for alterations in immune regulation and activation; and (3) cytokine induction of indoleamine 2,3-dioxygenase (IDO), thereby increasing kynurenine and kynurenine activation of the aryl hydrocarbon receptor (AhR) [ 5 ]. The current article reviews such processes and their implications for the understanding and treatment of SARS-CoV-2 pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation